(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines nominative sentences as independent one-member syntactic units in modern English. The paper discusses their grammatical status, communicative functions and the problem of predicativity in verbless constructions. Special attention is paid to the distinction between nominative sentences and elliptical structures, since nominative sentences are not incomplete variants of two-member sentences but self-sufficient units of communication. The article also analyzes the role of context, intonation and punctuation in creating predicative meaning. It is argued that nominative sentences are communicatively effective because they provide linguistic economy, sensory immediacy and strong emotional emphasis in literary, journalistic, conversational and advertising discourse.